2019
DOI: 10.14207/ejsd.2019.v8n3p261
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Microfinance Banks on the Growth of Small and Medium Enterprises in Lagos Metropolis

Abstract: Small and Medium Enterprises (SMEs) play a major role in the Nigerian economy, especially in terms of Employment, growth, productivity, and poverty alleviation. The purpose of this study was to examine the impact of Microfinance Banks (MFB) on the growth of SMEs in Lagos metropolis The data for this study was collected via questionnaires given to the owners of SMEs that had accounts with microfinance banks in Lagos metropolis. Out of 209 questionnaires distributed, 205 were viable and analyzed using the SPSS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
3
10
0
1
Order By: Relevance
“…Using the rating level of; (0 to ±0.3= Weak Relationship, ± 0.4 to ± 0.6= Moderate/ Average Relationship, ± 0.7 to ± 0.9= Very Strong Relationship) Table 1 indicates that there is a very strong positive relationship between micro loans banks and SMEs expansion at r= 0.912 and at level of significance 0.05, this implies that the micro finance banks provision of micro loans is significantly correlated to SMEs expansion. This is line with the previous findings of Gok (2019), Aladejebi (2019) and Khan (2021) Table 3 indicates that there is a very strong positive relationship between Micro savings and SMEs growth at r= 0.9 and at level of significance 0.05, this implies that the MFBs provision of business advisory services is significantly correlated to SMEs growth. This is line with the previous findings of Ogah-Alo, Kpor, Eneje (2019), Bulla, Maronga and Ngacho (2019), Aladejebi (2019) and Moussa (2020)…”
Section: Methodssupporting
confidence: 92%
“…Using the rating level of; (0 to ±0.3= Weak Relationship, ± 0.4 to ± 0.6= Moderate/ Average Relationship, ± 0.7 to ± 0.9= Very Strong Relationship) Table 1 indicates that there is a very strong positive relationship between micro loans banks and SMEs expansion at r= 0.912 and at level of significance 0.05, this implies that the micro finance banks provision of micro loans is significantly correlated to SMEs expansion. This is line with the previous findings of Gok (2019), Aladejebi (2019) and Khan (2021) Table 3 indicates that there is a very strong positive relationship between Micro savings and SMEs growth at r= 0.9 and at level of significance 0.05, this implies that the MFBs provision of business advisory services is significantly correlated to SMEs growth. This is line with the previous findings of Ogah-Alo, Kpor, Eneje (2019), Bulla, Maronga and Ngacho (2019), Aladejebi (2019) and Moussa (2020)…”
Section: Methodssupporting
confidence: 92%
“…The findings support H4. The study findings were consistent with the studies of Mutisya, Okibo & Olweny, (2014), Odetayo & Onaolapo (2016), Kipngetich (2019), Aladejebi (2019).…”
Section: Advisory Services and Economic Empowermentsupporting
confidence: 92%
“…Similar findings were also found by Almansour, et al (2019) who concluded that the existence of microfinance services had a significant impact on increasing the income of MSMEs. Similar research was also conducted by Aladejebi (2019) who found that the existence of microcredit had a positive impact on the development of MSMEs. Furthermore, Kartawinata, et al (2020) concluded that the existence of financing from financial institutions had a significant impact on income differences before and after receiving financing.…”
Section: Differences In Business Income Of Mekaar Customers In Kutasa...supporting
confidence: 71%